Application of Prototype Method on Student Monitoring System Based on WEB - April Lia Hananto; Bayu Priyatna; Asep Haris (Information System; Universitas Buana Perjuangan Karawang, 2020)
Public vocational school in Subang which continues to improve its academic activities, specifically in terms of improving student discipline related to student participation in school and improving student achievement. The collection of information about student participation and the value of new students delivered at the end of the semester compilation of report cards makes students who experience difficulties in the development of grades, meetings and student learning activities at school, for that we need a system that can help students to help guardians of students and the school in activities that involve students in school. In this research, we use a prototype method for system development. The advantage of the system built is that it can send attendance messages or student grades to enter no answers or get poor test scores for student guardians, student guardians can provide feedback on incoming information and make permits through the existing information system pages, the school also can use attendance data and grades to support activities at school.